Pemanfaatan Teknologi Robot dalam Peningkatan Kualitas Tidur dan Pencegahan Jatuh pada Lansia - Ida Faridah; Rr. Tutik Sri Hariyati; Etty Rekawaty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to answer whether the development of robotic technology can overcome the problem of sleep disorders and reduce the risk of falls in the elderly. The research method used is a non-systemic literature review that discusses robotic technology in elderly care. The research results show that from a study of 7 journals, the use of automated technology in providing care for older adults is beneficial. This technology is also able to reduce problems in older adults, one of which is sleep disturbance and the risk of falling. The use of this technology is not only beneficial for older adults but also beneficial for caregivers. In conclusion, using robotic technology in the senior service area, both at home and in hospitals or nursing homes, can reduce health risks in the elderly. Keywords: Older Adult, Robots